Modernizing Weather, Water, and Climate Services : A Road Map for Bhutan - World Bank Group (World Bank, Washington, DC, 2015)
The main objective of this technical assistance paper is to provide recommendations to the Royal Government of Bhutan for modernizing its hydrometeorological services, including capacity strengthening for disasterrelated early warning systems (EWSs). The DHMS does not have a national hydromet services policy but is in the process of preparing a strategic document to guide its modernization and institutional reform process. This technical assistance paper contributes to this process and proposes a road map for transforming the DHMS into a modern service delivery agency.